Mapas conceituais: um caminho para a aprendizagem significativa - Costa, Sandra Aparecida da (2009)
The aim of this work is to point out the contributions of conceptual maps and the Information and Communication Technologies (ICTs) as strategies in the construction of a significant learning. The intention is to head for the writing development of our students so that we can get contributions to the use of the Information and Communication Technologies in the school environment. As a theoretical fundamentation in the search for the comprehension of the subject, some writers as Jonassen, Moreira, Ontoria and Okada, give us subsidies so much that we can understand the concepts of conceptual maps, technology and significant learning. The research teacher and the fifth-grade students in tutorial situation of a public and elementary school participated in the research. We use the qualitative methodology in our work. At the end of this research, we have made it clear that to develop the concept of mapping, it is necessary to select, link, integrate, reorganize and open concepts so that the construction of the knowledge goes through the interaction, organization and share. The concept of construction is intrinsically linked to the concept of sharing. From this confirmation derives the proposal of the ampliation of this knowledge net to all the school scope from the ICTs that were important elements in the construction of the practice and researches route